Aplikasi Ecoprint untuk Mendukung Peningkatan Produktifitas Ekonomi Perempuan Desa Tarai Bangun: Ecoprint Application to Support Increasing Economic Productivity of Women in Tarai Bangun Village - Wahibah, Ninik Nihayatul; Martina, Atria; Zul, Delita; Yulminarti, Yulminarti; Meiwanda, Geovani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Most women in Tarai Bangun Village focus on their domestic activities. The community service program aimed to empower women in the enhancing of their economic productivity through gaining new skills such as the eco print technique. Ecoprint is an eco-friendly product, using parts of plants; therefore, it also inspires women to preserve the existence of local germplasm. The results of the program showed that all participants were able to make ecoprint products. They also were satisfied with this program. However, the drawback of this program is that our partners need to understand marketing techniques.